2016
DOI: 10.1161/circresaha.116.308384
|View full text |Cite
|
Sign up to set email alerts
|

AT 2 Receptor Activation Prevents Sodium Retention and Reduces Blood Pressure in Angiotensin II–Dependent Hypertension

Abstract: Rationale Compound 21 (C-21) is a highly selective non-peptide angiotensin AT2 receptor (AT2R) agonist. Objective To test the hypothesis that chronic AT2R activation with C-21 induces natriuresis via an action at the renal proximal tubule (RPT) and lowers blood pressure (BP) in experimental angiotensin II (Ang II)-dependent hypertension. Methods and Results In rats, Ang II infusion increased both sodium (Na+) retention and BP on Day 1 and BP remained elevated throughout the 7 day infusion period. Either in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
55
1
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 56 publications
(61 citation statements)
references
References 45 publications
4
55
1
1
Order By: Relevance
“…Interestingly, C-21 significantly increased 24h urine Na + excretion in both control and HSD-fed animals chronically (on days 11–14 of the study) (**43). This observation is similar to earlier findings of an enhanced natriuresis in response to C-21 at 2 weeks in this model (42) and is reminiscent of the chronic negative Na + balance induced by C-21 in the Ang II infusion model of experimental hypertension (**28), with obese Zucker rats and Ang II-infused rats having increased Ang II levels in common. Thus, pathophysiologic states characterized as having an activated RAS may respond best to the chronic natriuretic and BP lowering power of AT 2 R activation.…”
Section: Beneficial Effects Of At2r Activation In Obesity/metabolic Ssupporting
confidence: 90%
See 3 more Smart Citations
“…Interestingly, C-21 significantly increased 24h urine Na + excretion in both control and HSD-fed animals chronically (on days 11–14 of the study) (**43). This observation is similar to earlier findings of an enhanced natriuresis in response to C-21 at 2 weeks in this model (42) and is reminiscent of the chronic negative Na + balance induced by C-21 in the Ang II infusion model of experimental hypertension (**28), with obese Zucker rats and Ang II-infused rats having increased Ang II levels in common. Thus, pathophysiologic states characterized as having an activated RAS may respond best to the chronic natriuretic and BP lowering power of AT 2 R activation.…”
Section: Beneficial Effects Of At2r Activation In Obesity/metabolic Ssupporting
confidence: 90%
“…Building on the findings that acute AT 2 R activation induces natriuresis, Kemp et al (**28) demonstrated in the Ang II infusion model of experimental hypertension that chronic AT 2 R activation with C-21 prevented the initial (24h) Ang II-induced reduction in Na + excretion, induced sustained negative Na + balance and lowered BP to near-control levels during a 7-day infusion period. As with acute C-21 administration, concurrent AT 1 R blockade was not required to unmask the natriuretic and hypotensive actions of chronic C-21.…”
Section: At2r Agonist - Induced Natriuresis and Bp Reductionmentioning
confidence: 99%
See 2 more Smart Citations
“…AT2 receptor stimulation causes vasorelaxation through protein kinase A (PKA)-dependent endothelial nitric oxide (NO) synthase (eNOS) activation or paracrine signaling induced by bradykinin/NO/cyclic GMP production (1, 8). Mice overexpressing the AT2 receptor exhibit vasodilation (11), and pharmacological stimulation of AT2 receptor promotes natriuresis, lowering of blood pressure, and inhibits AngII-mediated hypertension (12, 13). In systemic AT2 receptor transgenic mice with AngII infusion, perivascular fibrosis but not cardiac hypertrophy is attenuated compared with wild-type mice (14).…”
Section: Introductionmentioning
confidence: 99%